MiR-155 is Involved in Renal Ischemia-Reperfusion Injury via Direct Targeting of FoxO3a and Regulating Renal Tubular Cell Pyroptosis - Haoyu Wu; Tao Huang; Liang Ying; Conghui Han; Dawei Li; Yao Xu; Ming Zhang; Shan Mou; Zhen Dong (Cellular Physiology and Biochemistry, 2016)
Background/Aims: Ischemia/reperfusion injury (IRI) plays a crucial role in renal transplantation and can cause renal failure associated with pyroptosis, a pro-inflammatory-induced programmed cell death. Small endogenous non-coding RNAs have been shown to be involved in renal ischemia/reperfusion injury. This study was performed to investigate which miRNAs regulate pyroptosis in response to renal ischemia/reperfusion injury and determine the mechanism underlying this regulation. Methods: An in vivo rat model of renal IRI was established, and the serum and kidneys were harvested 24 h after reperfusion to assess renal function and histological changes. For the in vitro study, the cultured human renal proximal tubular cell line HK-2 was subjected to 24 h of hypoxia (5% CO2, 1% O2, and 94% N2) followed by 12 h of reoxygenation (5% CO2, 21% O2, and 74% N2). The mRNA expression levels were analyzed by real-time PCR, and the protein expression levels were analyzed using Western blot, immunofluorescence staining and enzyme-linked immunosorbent assay (ELISA). Bioinformatics analyses were applied to predict miR-155 targets, which were then confirmed by a luciferase reporter assay. Results: We found that the levels of pyroptosis-related proteins, including caspase-1, caspase-11, IL-1β and IL-18, were significantly increased after renal ischemia/reperfusion injury. Similarly, hypoxia-reoxygenation injury (HRI) also induced pyroptosis in HK2 cells. Furthermore, our study revealed that miR-155 expression was substantially increased in the renal tissues of IRI rats and in HRI HK2 cells. Up-regulation of miR-155 promoted HK2 cell pyroptosis in HRI; conversely, knockdown of miR-155 attenuated this process. To understand the signaling mechanisms underlying the pro-pyroptotic activity of miR-155, we found that exogenous expression of miR-155 up-regulated the expression of caspase-1 as well as the pro-inflammatory cytokines IL-1β and IL-18. Moreover, miR-155 directly repressed FoxO3a expression and its downstream protein apoptosis repressor with caspase recruitment domain (ARC). Conclusions: Our study proposes a new signaling pathway of miR-155/FoxO3a/ARC leading to renal pyroptosis under ischemia/reperfusion injury conditions.